Plants used for reproductive health by women of Lavezares, Northern Samar - Cometa, Fiona G.; Mahinay, Teresa S. (2011)
This paper reports the reproductive health problems and medicinal plants used by women of Lavezares, Northern Samar. The objectives of this study is to determine the reproductive health problems of women in Lavezares, Northern Samar, to identify the plant parts used and their modes of preparation. The respondents of this study were the Barangay Health Workers of the municipality who were known to posses more knowledge in the use of medicinal plants. The data was gathered using a semi-structured and unstructured interview. The reproductive health problems among the women of Lavezares, Northern Samar are those related to menstruation, pregnany/conception, child birth, post partum, menopause, and contraception. Thirty-eight medicinal plants belonging to 23 families used to treat reproductive health problems were identified.ll plant parts, aerial as well as underground parts are used in medical applications. In some instances the whole plant is utilized (2.43%). Most of the species are harvested for their lives (41.46%) and the whole shoot (29.27%), also by the seeds (7.32%) and stems (7.32%), then by the fruits (7:31%), and lastly by the roots (4.88%). The principal methods of remedy preparation were reported to be through decoction(60.98%), steaming (9.76%), cooking as in a dish (9.76%), concuccion (9.76%), pounding (7.32%, and no specific preparation (2.44%).
Undergraduate thesis (B.S. Biology) -- University of the Philippines, Tacloban.
Keywords: Science and Technoloy